Comparative Antidiabetic Investigation of Talapotaka Churna and Avartaki Churna in STZ-Induced Diabetic Rats (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To compare the antidiabetic effect of Talapotaka Churna and Avartaki Churna in experimental animals. Materials and Methods: Talapotaka Churna (Avartaki [Cassia auriculata L.], Amalaki [Emblica officinalis G.], Haridra [Curcuma longa L.], and Daruharidra [Berberis aristata]) and Avartaki Churna (C. auriculata L.) were prepared by the standard procedure of Churna Kalpana. Diabetes was induced by streptozotocin (35 mg/kg) solution (intra-peritoneal). After assessment of hyperglycemia as an approximate induction of diabetes, a group of animals (TP300 and AV300) were treated with a dose of 300 mg/kg of Talapotaka Churna and Avartaki Churna each. For treatment comparison, Group III animals were treated with a standard antidiabetic drug, glibenclamide 1 mg/kg. Blood sugar and lipid profile level were estimated biochemically. Results: Talapotaka Churna and Avartaki Churna both reduced fasting blood glucose significantly on various doses in STZ-induced diabetic rats. Talapotaka Churna and Avartaki Churna also showed a reduction in the levels of total cholesterol, triglycerides, low-density lipoprotein-cholesterol, very low-density lipoprotein‑cholesterol but it increases the levels of high-density lipoprotein‑cholesterol in diabetic rats. Conclusion: Talapotaka Churna and Avartaki Churna have significant antidiabetic and antihyperlipidemic activities in Type 2DM rats, which seem to scientifically validate its traditional uses and might be promising drugs in the therapy of diabetes mellitus and its hyperlipidemic complications